Analisis Potensi Pengembangan Wisata Dan Kuliner Untuk Pariwisata Berkelanjutan Di Lereng Gunung Kawi: Studi Pada Desa Bangelan - Teddy Chandra; Warta Sumirat; Dadang Suratman; Sukarno Wibowo; Christian Helmy Rumayar (Penerbit Lafadz Jaya, 2026)
This study aims to analyze various tourism potentials and various local culinary delights on the slopes of Mount Kawi c.q Bangelan Village which have the potential to be developed as a form of sustainable tourism development. The objectives of this study are: 1) to determine the description of Bangelan Village, Malang Regency; 2) to determine the description of tourism potential in Bangelan Village, Malang Regency; and 3) to determine the description of local culinary delights in Bangelan Village, Malang Regency. This study was conducted using qualitative research methods. Data collection techniques used were: 1) literature study; 2) observation; and 3) interviews. Data analysis was carried out descriptively. The results of the study indicate that Bangelan Village, Wonosari District, Malang Regency, which is located on the slopes of Mount Kawi, has several potential tourist destinations to be developed, namely: blue water tourism, Tanaka Waterfall tourism, mubeng deso offroad jeep special interest tour, Bangelan garden tourism, coffee education tourism, goat farming education tourism, tilapia fish pond education tourism. In addition, Bagelan village also has a variety of culinary delights that have the potential to be developed, such as: Bangelan robusta coffee, banana chips, jackfruit chips, mango chips, snake fruit chips, various vegetable chips, and Etawa goat's milk.